Evaluation of Multi-Function Drainage Channels For Running Water Fish Culture For The Benefit of The Community In Pangururan District - Manoktong Sianturi, Novdin (International Journal of Engineering, Science and Information Technology, 2022)
Pangururan Subdistrict in Samosir Regency requires rearranging its open land functions related to the meaning of the environment. From the civil engineering perspective, landslides can occur suddenly during the rainy season without being noticed by the people around the Pangururan sub-district, Samosir Regency. To realize this program, the community can add the function of the drainage channel into a mobile fish pond around the Pangururan Subdistrict, Samosir Regency, which still has a large area of land/settlements to become a running fish pond drainage channel. This can increase residents' income which is beneficial for the community around the drainage canal. In addition, the problem of overflowing water in the rainy season will be minimized. To implement this program, an analysis should be prepared in advance to evaluate the drainage channel that will function as a fish pond around Pangururan District, Samosir Regency. In line with the government's program in promoting and increasing the income of residents, the existing drainage channels should be utilized. Unproductive drainage channels can become productive drainage channels by cultivating freshwater fish along the drainage channel while simultaneously irrigating rice fields. Therefore, a wet section of the plan is made along 1000 meters where the condition of the drainage channel is planned according to the analysis. The depth of the drainage channel for running water fish ponds is 100 to 170 cm and the width of the top side from 100 cm to 150 cm, and the width of the sides below 100 cm. Based on the calculations, the first process that must be done is to first calculate the maximum planned rainfall, calculate the planned discharge, calculate the dimensions of the channel, and flood discharge (designated discharge), where QT = 0.278 x C x I x A = 6.69 m3/s at a speed of plan average flow. The flow velocity of the drainage channel is installed with a sluice so that the average velocity value is = 1/n R2/3 x S1/2 = 3.8 m/s, the cross-sectional area of a fish pond with a wet cross-section A = a x b = 1.904 m2, the cross-sectional area of the wet plan making fish ponds where the channel design discharge for fish ponds is QS = AS x V = 7.23 m3/s and the calculation of sluice gates with a width of 50 cm and a height of 170 cm for fish pond water with Q = (u x b x a Â ) x 3 of 10.8 m/s.